Carlos Alberto Moreyra, Los criptogramas de Santa Teresa. Ed. del Autor, Córdoba (Argentina), 1964; 39 pp. - Alatorre, Antonio (Nueva Revista de Filología Hispánica (NRFH), 1970)
Se reseñó el libro: Los criptogramas de Santa Teresa.